Improving smoking cessation after myocardial infarction by systematically implementing evidence-based treatment methods: a prospective observational cohort study. (14th October 2021) - Leosdottir, M; Warjerstam, S; Ogmundsdottir Michelsen, H; Schlyter, M; Hag, E; Wallert, J; Larsson, M
Abstract: Background: For smokers who suffer a myocardial infarction (MI), smoking cessation is the most effective measure to reduce recurrent event risk. Still, evidence-based treatment methods for aiding smoking cessation post-MI are underused. Purpose: To compare the odds of smoking cessation at two-months post-MI before and after implementing a set of pre-specified routines for optimization of evidence-based treatment methods for smoking cessation, with start during admission. Methods: Structured routines for early smoking cessation counselling and treatment optimization were implemented at six cardiac rehabilitation (CR) centres in Sweden. The routines included CR nurses providing current smokers hospitalized for acute MI with short consultation, written material, and optimal dosage of nicotine replacement therapy during admission, increasing early prescription of varenicline for eligible patients, and contacting the patients by telephone 3–5 days after discharge, after which usual care CR follow-up commenced. Centres were also encouraged to strive for continuity in nurse-patient care. Patient data was retrieved from the SWEDEHEART registry and medical records. Using logistic regression, we compared the odds for smoking cessation at two-months post-MI for currently smoking patients admitted with MI (a) before (n=188, median age 60 years, 23% females) and (b) after (n=195, median age 60 years, 29% females) routine implementation. Secondary outcomes included adherence to implemented routines and the association of each routine with smoking cessation odds at two-months. Results: In total, 159 (85%) and 179 (92%) of enrolled patients attended the two-month CR follow-up, before and after implementation of the new routines. After implementation, a significantly larger proportion of patients (65% vs 54%) were abstinent from smoking at two-months (crude OR 1.60 [1.04–2.48], p=0.034) (Figure 1). Including only those counselled during admission (n=89), 74% (vs 54%) were abstinent at two-months (crude OR 2.50 [1.42–4.41], p=0.002). After the new routine implementation patients were counselled more frequently during admission (50% vs 6%, p<0.001), prescribed varenicline at discharge or during follow-up (23% vs 7%, p<0.001), and contacted by telephone during the first week post-discharge (18% vs 2%, p<0.001), compared to before implementation. Crude and adjusted associations between each routine and smoking cessation at two-months are shown in Table 1. Entering all routines into the regression model simultaneously, being prescribed varenicline before discharge or during follow-up had the strongest independent association with smoking abstinence at two-months (adjusted OR 4.09 [1.68–10.00], p=0.002). Conclusion: Our results support that readily available methods for aiding smoking cessation can be implemented effectively in routine practice, with possible beneficial effects on smoking cessation for the high-risk group of smoking MI patients. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Swedish Heart and Lung AssociationPfizer AB